Variabilidade ecofisiológicas da germinação em physalis L. E em espécies de solanum L. Neotropicais - Lima, Saulo Antonio Alves de (2017)
The Solanaceae family comprises approximately 2.500 species and about 100 genera distributed throughout the tropical and temperate regions of the globe. The Solanum genus, the largest in the family, comprises about 1.500 species, some of them of economic importance such as crops, medicinal plants, toxic or invasive. Most of the studies dealing with germination of Solanum are restricted to species of agricultural, toxic or medicinal importance, and no in depth studies on native species are recognized. In this work, the germination and vigor of seeds of Solanum wild species, as well as Physalis angulata, were analyzed using two constant temperatures (20 and 30°C) and an alternating temperature of (20-30°C) and seeds kept in a substrate of paper roll and gerbox boxes. In general, all species presented better vigor and germination at the alternate temperature, with variable results regarding the substrate, although with a slight superiority to the seeds in the paper roll substrate. On the other hand, the values obtained for vigor and twinning in the other species were unsatisfactory, suggesting that the conditions of the experiment were not enough to provide the dormancy in these species.